THE EFFECTIVENESS OF IMPLEMENTING A SLIMS-BASED LIBRARY AUTOMATION SYSTEM IN THE REGIONAL PUBLIC LIBRARY OF TANAH DATAR REGENCY - Dodi Nofri Yoliadi (UPT. Perpustakaan Universitas Muhammadiyah Ponorogo, 2023)
This research was conducted to obtain information about the effectiveness of using the SLIMS-based library automation system by librarians at the Tanah Datar District Public Library and to identify the obstacles encountered in its use. In this study, descriptive research was combined with a qualitative approach using the SLIMS-based library automation system by librarians at the Tanah Datar District Public Library and to identify the obstacles encountered in its use. In this study, descriptive research was combined with a qualitative approach. Based on research findings, the effectiveness of using the SLIMS-based library automation system at the Tanah Datar District Public Library in various forms of library activities includes the procurement and processing of library materials, fast circulation processes, and librarian satisfaction with the use of the SLIMS-based library automation system. Based on indicators measuring the effectiveness of implementing the SLIMS-based library automation system, such as data security, time, accuracy, relevance, variety of reports, physical comfort, information quality, and information technology, it is proven that, after using the SLIMS-based library automation system, library management and services to users as a whole run more effectively and efficiently.